Hope for the forgotten poor: Chinese male migrants, affective labor and the livestreaming industry - Tsang, Eileen Y. H.; Wilkinson, Jeffrey S. (Frontiers in Sociology, 2025)
In 2020, China's live-streaming industry reached an audience estimated to be 587 million users, which generated 961 billion yuan (Zixun, 2021). This technological transition to online commerce has enabled marginalized rural youth opportunities for career advancement and financial success as livestreamer hosts. This study examines how rural migrants capitalize on their affective labor to successfully engage their fans and supporters. Livestreaming guilds (zhibo gonghui 直播公會) play a pivotal role in recruiting, training, and managing online host personalities. Guilds monitor and manage the livestreamers by providing official reports of audience size, sales, and even how well the livestreamer performs. The career experiences of 62 rural-to-urban heterosexual male migrant livestreamers in China are examined. Affective labor is an immaterial form of labor that manipulates affect to generate feelings such as satisfaction, excitement, or passion in others. This article operationalizes affective labor to male heterosexual livestreamers using three distinct lenses: (1) sensuous dispositions tied to city life; (2) livestreamers' use of affective labor to maintain close relationships with their big tippers; (3) the relationships with the guilds and how livestreamers leverage affective labor to navigate their success and risks. This article offers a broadened perspective of rural-to-urban migrants in China. Through examining how young migrants become live-streamers, this article can provide insights into the evolving field of labor studies.